Respuesta :

Answer:

(f - g)(x)= - 6 {x}^{2} - 8x + 9

(f - g)(-4!)= - 55

Step-by-step explanation:

[tex]f(x) = - 9 {x}^{2} - 2x, \: \: g(x) = - 3 {x}^{2} + 6x - 9 \\ (f - g)(x) = f(x) - g(x) \\ = - 9 {x}^{2} - 2x - (- 3 {x}^{2} + 6x - 9) \\ = - 9 {x}^{2} - 2x + 3 {x}^{2} - 6x + 9 \\ \purple{ \boxed{ \bold{(f - g)(x)= - 6 {x}^{2} - 8x + 9}}} \\ (f - g)( - 4)= - 6 {( -4 )}^{2} - 8( - 4) + 9 \\ = - 6 \times 16 + 32 + 9 \\ = - 96 + 41 \\ \red{ \boxed{ \bold{(f - g)( - 4)= - 55}}}[/tex]

ACCESS MORE